2009
DOI: 10.1002/hbm.20868
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive optical measures of CBV, StO2, CBF index, and rCMRO2 in human premature neonates' brains in the first six weeks of life

Abstract: With the causes of perinatal brain injuries still unclear and the probable role of hemodynamic instability in their etiology, bedside monitoring of neonatal cerebral hemodynamics with standard values as a function of age are needed. In this study, we combined quantitative frequency domain near infrared spectroscopy (FD-NIRS) measures of cerebral tissue oxygenation (StO 2 ) and cerebral blood volume (CBV) with diffusion correlation spectroscopy (DCS) measures of a cerebral blood flow index (CBF ix ) to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
199
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 65 publications
6
199
1
1
Order By: Relevance
“…It has been reported that CBV increases with postconceptional age and that the relationship between these variables can be explained by the results of anatomical studies of cerebral blood vessels [15,20]. These previous reports support the current findings, as the mean GAs of infants from the studies which showed relatively low CBVs (1.7-1.97 ml/100 g) [9,19] were shorter than those from studies which showed relatively high CBVs (2.31-2.45 ml/100 g) [15]. The reason for the higher CBV values obtained by continuous wave NIRS than those obtained in this study is unclear, even taking into account the immaturities of the preterm infants (mean GA, 29 weeks) [4,8].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It has been reported that CBV increases with postconceptional age and that the relationship between these variables can be explained by the results of anatomical studies of cerebral blood vessels [15,20]. These previous reports support the current findings, as the mean GAs of infants from the studies which showed relatively low CBVs (1.7-1.97 ml/100 g) [9,19] were shorter than those from studies which showed relatively high CBVs (2.31-2.45 ml/100 g) [15]. The reason for the higher CBV values obtained by continuous wave NIRS than those obtained in this study is unclear, even taking into account the immaturities of the preterm infants (mean GA, 29 weeks) [4,8].…”
Section: Discussionsupporting
confidence: 81%
“…The study showed that the CBV in term infants was significantly higher than that in preterm infants during the first 3 days of life. There have been several studies on CBV in neonates measured by NIRS [4,8,9,15,19]. The CBVs of infants obtained using NIRS in these previous studies are summarized in table 2.…”
Section: Discussionmentioning
confidence: 99%
“…DCS is a relatively new technique which can directly probe blood flow in deep tissues including the cerebral cortex (Cheung et al, 2001;Culver et al, 2005;Dietsche et al, 2007;Durduran et al, 2009Durduran et al, , 2010Edlow et al, 2010;Gagnon et al, 2008;Li et al, 2008;Shang et al, 2011a,b;Zirak et al, 2010). Blood flow variations measured by DCS have been validated in various organs and tissues against other standards, including Doppler ultrasound (Roche-Labarbe et al, 2010), power Doppler ultrasound (Yu et al, 2005), laser Doppler (Durduran, 2004;Shang et al, 2011a), Xenon-CT , fluorescent microsphere measurement , and perfusion MRI (Yu et al, 2007). The hybrid NIR optical instrument offers direct and simultaneous measurements of CBF and cerebral oxygenation in microvasculature within the same region of cerebral cortex, which may bring new and informative insights about LFOs in local brain tissues.…”
Section: Introductionmentioning
confidence: 98%
“…Cortical blood flow was measured with a home-built diffuse correlation spectroscopy (DCS) system employing a solid-state long coherence length laser at 785 nm for illumination and four photon-counting avalanche photodiodes for detection, as previously described [8]. The intensity auto-correlation function of each channel is computed by a digital correlator and the cerebral blood flow index (CBF i ) is determined by fitting the measured electric field autocorrelation functions to a model of dynamic light scattering in deep tissues.…”
Section: Methodsologymentioning
confidence: 99%
“…Cortical blood flow was measured with a home-built diffuse correlation spectroscopy (DCS) system employing a solid-state long coherence length laser at 785 nm for illumination and four photon-counting avalanche photodiodes for detection, as previously described [8]. The intensity auto-correlation function of each channel is computed by a digital correlator and the cerebral blood flow index (CBF i ) is determined by fitting the measured electric field autocorrelation functions to a model of dynamic light scattering in deep tissues.The cerebral metabolic rate of oxygen index (CMRO 2i ) was estimated as previously described [8]. For these experiments, an assumption of baseline total hemoglobin concentration of 100 M at 60% oxygen saturation was used to convert the changes in hemoglobin concentrations measured by the CW into estimated absolute concentrations required for calculating the OEF.…”
mentioning
confidence: 99%